IMF Survey, Volume 30, Issue 12. (IMF Survey; IMF Survey ;, 2001)
On June 7, IMF Managing Director Horst Kohler announced the appointments of the new First Deputy Managing Director and three department heads. The full text of IMF Press Release No. 01/27 is available on the IMF's website (www.imf.org).